The influence of cultural value in organisation: a study in local and anglo-american firms in Malaysia - Zainuddin, S.; Isa, C.R. (2011)
The budgeting process is argued to be very much influenced by the organisational culture that exists within an organisation. By employing Hofstede’s (1980) cultural dimension of power distance, this study aims to provide the current power distance index in Malaysia and the score of power distance and budget participation level in local and foreign firms operating in Malaysia. It also attempts to provide empirical evidence for the role of power distance as moderating variable in the relationship between budget participation and motivation. The overall results show that Malaysian firms scored a moderate level of power distance index. Contrary to earlier expectation, there is no significant difference in the level of power distance and the level of participation in budgeting process in local and foreign firms. Budget participation also does not moderate the relationships between budget participation and motivation.